РАСЧЕТНЫЙ СОПОСТАВИТЕЛЬНЫЙ АНАЛИЗ ОДНОФАЗНЫХ ПЕРЕМЕШИВАТЕЛЕЙ ЖИДКОГО МЕТАЛЛА - Глухенький, А.И.; Гориславец, Ю.М.; Токаревский, А.В.; Максименко, В.Ю. (Інститут електродинаміки НАН України, Київ, 2015)
The computer 3D modelling of electromagnetic and hydrodynamic processes in electromagnetic system consisting of single-phase stirrer and liquid metal in bath reverberatory furnace is executed. The electromagnetic problem for such system is solved by numerical calculation of differential equations for the magnetic vector and scalar electric potentials. The hydrodynamic problem is solved by calculation of the Navies-Stokes equations for turbulent flow using the k-ε model. The stirrer design options in the form of single-phase inductor with П- and Ш-shaped ferromagnetic cores is considered. It is shown that at the same ampere-turns and feeding them commercial frequency current, they provide practically the identical vortex liquid metal flow in structure and intensity, although the total network power consumption in the second case approximately 2-fold higher The considerable differences between these inductors in power action on liquid metal and in nature of its motion in furnace bath were found at low supply current frequency (below 20 Hz). References 5, figures 4.